School autonomy with accountability as a cross-national policy model: diverse adoptions, practices and impacts - Antoni Verger; Lluís Parcerisa; Marcel Pagès; Marjolein Camphuijsen (Taylor & Francis Group, 2024)
This special issue examines the policy model of School Autonomy with Accountability (SAWA) and its diverse configurations . The focus is on understanding how SAWA reforms shape governance practices and influence educational systems in different educational settings. Drawing on a range of theoretical perspectives, the issue explores how political factors, administrative traditions, and local professional frameworks shape the adoption and evolution of these policies. SAWA reforms promote school autonomy in decision-making while holding schools accountable for performance outcomes through various instruments such as standardized assessments, school improvement projects, and accountability arrangements. However, these policies often create tensions between autonomy and accountability, and their implementation produces varied outcomes depending on local contexts and institutions. The issue also highlights the growing role of data use in educational decision-making and examines the challenges associated with policy enactment at the school level. Taking stock of these discussions, in this introduction to the special issue, we delve into the complexities of SAWA reforms and their implications for educational equity, innovation, and governance. We also highlight the need for further research into the dynamic interaction between the formulation of SAWA policies and their local implementation, particularly in underexamined national contexts.